Interaksi Edukatif dalam Pendidikan Agama Islam dan Dampaknya Terhadap Motivasi Belajar Siswa di Sekolah Dasar dan Sekolah Menengah Pertama - Muhajir Muhajir; Ismail Ismail; Indrawan Tobarasi (TADRIBUNA: Journal of Islamic Education Management, 2025)
This study aims to analyze the forms of educative interaction in Islamic Religious Education (PAI) learning and its impact on students’ learning motivation at SD–SMP Negeri Satap 7 Konawe Selatan. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and documentation, and then analyzed using the Miles and Huberman model. The findings reveal that educative interaction occurs through the use of two-way communication, group discussions, individual guidance, project-based learning, and teacher role-modeling. Positive and humanistic interactions were proven to enhance students’ learning motivation, as reflected in increased classroom participation, self-confidence, interest in religious practices, and commitment to completing assignments. However, the effectiveness of educative interaction is influenced by several barriers, including differences in students’ academic abilities, limited mastery of active learning methods, psychological challenges among students, and inadequate learning facilities. To overcome these obstacles, teachers implemented various learning strategies, provided rewards, applied personal approaches, and strengthened collaboration with parents. This study confirms that educative interaction is a key component in the success of PAI learning and the development of students’ learning motivation and religious character.